Targeted Delivery of the HLA-B∗27-Binding Peptide into the Endoplasmic Reticulum Suppresses the IL-23/IL-17 Axis of Immune Cells in Spondylarthritis - Hui-Chun Yu; Kuang-Yung Huang; Ming-Chi Lu; Hsien-Lu Huang; Su-Qin Liu; Ning-Sheng Lai; Hsien-Bin Huang (Mediators of Inflammation)
Ankylosing spondylitis (AS) is highly associated with the expression of human leukocyte antigen-B27 (HLA-B∗27). HLA-B∗27 heavy chain (B27-HC) has an intrinsic propensity to fold slowly, leading to the accumulation of the misfolded B27-HC in the endoplasmic reticulum (ER) and formation of the HLA-B∗27 HC homodimer, (B27-HC)2, by a disulfide linkage at Cys-67. (B27-HC)2 displayed on the cell surface can act as a ligand of the killer-cell Ig-like receptor (KIR3DL2). (B27-HC)2 binds to KIR3DL2 of NK and Th17 cells and activates both cells, resulting in the activation of the IL-23/IL-17 axis to launch the inflammatory reaction in AS patients. However, activation of the IL-23/IL-17 axis originally derived from the HLA-B∗27 misfolding in the ER needs to be characterized. In this study, we delivered two HLA-B∗27-binding peptides, KRGILTLKY and SRYWAIRTR, into the ER by using a tat-derived peptide (GRKKRRQRRR)-His6-ubiquitin (THU) vehicle. Both peptides are derived from the human actin and nucleoprotein of influenza virus, respectively. Our results demonstrated that targeted delivery of both HLA-B∗27-binding peptides into the ER can promote the HLA-B∗27 folding, decrease the levels of (B27-HC)2, and suppress the activation of the IL-23/IL-17 axis in response to lipopolysaccharide. Our findings can provide a new therapeutic strategy in AS.